Trade and intergenerational income mobility: Theory and evidence from the U.S. - Italo Colantone; Gianmarco I. P. Ottaviano; Kohei Takeda (Fondazione Eni Enrico Mattei (FEEM), 2024)
This paper studies the impact of globalization on intergenerational income mobility. Exploiting U.S. data, we find that stronger trade exposure at the commuting zone level lowers the intergenerational income mobility of residents. In particular, higher exposure to Chinese import competition lowers the income mobility of the cohort of U.S. workers born in 1980-1982. We present a general equilibrium theory in which path dependence in sector choice of individuals over generations and mobility frictions determine the dynamics of industrial compositions across locations in a country. The theory predicts that rising import competition reduces intergenerational income mobility, consistent with the empirical findings.
Keywords: F1; F14; F16; 330; Import competition; Distributional consequences; Intergenerational income mobility